Interrelationship of thermal and mechanical properties of poly(ethylene terephthalate)/poly(ethylene 2, 6‐naphthalate)/graphene nanocomposites. Issue 3 (28th June 2015) - Ghadami, Azam; Ehsani, Morteza; Khonakdar, Hossein Ali
Abstract : In the present work, attempts were made to investigate the thermal and mechanical properties of melt‐processed poly(ethylene terephthalate) (PET)/poly(ethylene 2, 6‐naphthalate) (PEN) blends and its nanocomposites containing graphene by using differential scanning calorimetry and tensile test experimenting. The results showed that crystallinity, which depends on a blend ratio, completely disappeared in a composition of 50/50. By introducing graphene to PET, even in low concentrations, the crystallinity of samples increased, while the nanocomposite of PEN indicated reverse behavior, and the crystallinity was reduced by adding graphene. In the case of PET‐rich (75/25) nanocomposite blends, by increasing the nano content in the blend, the crystallinity of the samples was enhanced. This behavior was attributed to the nucleating effect of graphene particles in the samples. From the results of mechanical experiments, it was found in PET‐rich blends that by increasing the PEN/PET ratio, the modulus of samples decreased, whereas in the case of PEN‐rich blends, a slight increment of modulus is seen as a result of the increment of the PEN/PET ratio. The two contradicting behaviors were attributed to the reduction of crystallinity of PET‐rich blends by enhancement of PEN/PET ratio and the rigid structure of PEN chains in PEN‐rich blends. Unlike the different modulus change of PET‐rich and PEN‐rich blends, the nanocomposites of these blends similarly indicated an increment of modulus and characteristics of rigid materials by increasing the nano content. Furthermore, the same behavior was detected in nanocomposites of each polymer (PET and PEN nanocomposites). The alteration from ductile to rigid conduction was related to the impedance in the role of graphene plates against the flexibility of polymer chains and high values of graphene modulus. J. VINYL ADDIT. TECHNOL., 23:210–218, 2017. © 2015 Society of Plastics Engineers